THE PECULIARITIES OF SOCIAL AND LIVING SKILLS FORMATION OF PRESCHOOLERS WITH TYPICAL DEVELOPMENT AND CHILDREN'S CEREBRAL PALSY - Tamara Romenska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is dedicated to the analysis of the current state of theory and practice of formation of social and living skills of children with typical development and with cerebral palsy. Contents of educational and developmental programs, designed on the ground of State basic component of preschool education has been analyzed in the aspect of formation of social and living skills of preschool children with typical development. Contents of programs for children with special needs (with musculoskeletal system dysfunction, mental deficiency and mental retardation) has been revealed in the part concerning matters of formation of social and living skills by preschool children with cerebral palsy. Necessity to develop modern program and educational and methodological support for formation of social and living skills by preschool children with cerebral palsy has been substantiated. Author's sight of contents of formation of social and living skills by preschool children with cerebral palsy has been revealed according to principles of complexity, integration and based on interdisciplinary approach.